Pengaruh Tingkat Kecukupan Modal, Likuiditas, dan Risiko Kredit terhadap Profitabilitas Bank Pembangunan Daerah - Wildan Army Abdillah; Muhammad Iqbal Nurfauzan (Jurnal Inovasi Bisnis dan Kewirausahaan, 2022)
The purpose of this paper is to analyze the effect of the level of capital adequacy. Liquidity, and credit risk to bank profitability. The data collected is data from Regional Development Banks as a population and obtained 22 Regional Development Banks as samples and 242 observational data. Sampling through purposive sampling technique with multiple regression analysis method with the help of Eviews version 9. The results of this study indicate that partially the level of capital adequacy as proxied by Capital Adequacy Ratio and liquidity as proxied by Current Ratio has no effect on profitability as proxied using return on assets. Meanwhile, non-performing loans as credit risk have a significant effect on profitability.